Investigation of numerical technique to evaluate frequency response analysis (FRA) data measurement of auto power transformer - Hashim, Nurul ‘Izzati (2013)
Power and distribution transformers are expensive and important units in electric power networks. Majority of dielectric and mechanical failures in transformers are due to mechanical displacements in the winding structure. Detection of these winding displacements in advance of a dielectric failure can reduce unplanned maintenance costs and provide the possibility to improve system reliability by preventing outages and breakdowns. Frequency Response Analysis (FRA) is a powerful and sensitive diagnostic test technique to evaluate transformer winding displacements by measuring their electrical transfer functions over a wide frequency range. In the past, it has really required trained experts to interpret the FRA test results in a subjective manner to make a judgement as whether the amount of agreement or disagreement between the two or more sets of FRA measurements is significant enough for further testing and inspection of the transformer. Therefore, a quite number of numerical techniques have been proposed to analyze the FRA data such as Standard Deviation (SD), Absolute Sum of Logarithmic Error (ASLE), Correlation Coefficient (CC), and others. Several of the numerical techniques were evaluated for its suitability, reliability and sensitivity for different cases of auto power transformer, 1000 MVA, 400/ 275/ 13 kV HV neutral winding terminations and comparison methods. It is concluded that Absolute Sum of Logarithmic Error (ASLE) is more reliable and sensitive. The ASLE technique should included as an analysing technique in any FRA test to get better interpretation and increase opportunities to provide more objective comparison of FRA test results.